Praktik Penyewaan Lahan Perkebunan Tanpa Perjanjian tertulis Ditinjau dari Perspektif Hukum Ekonomi Syariah (Studi di Kecamatan Gunung Labuhan) - Winda Anggraini (CV. Creative Tugu Pena, 2024)
The purpose of this study is to determine the practice of renting plantation land without a written agreement reviewed from the perspective of Islamic economic law in the Gunung Labuhan District community. This study is included in the type of qualitative research. Data collection techniques used by researchers include observation, interviews, and documentation. After the data is collected, the analysis is carried out using a descriptive qualitative method. Based on the results of the study, it can be concluded that the implementation of plantation land rental activities in Gunung Labuhan District is usually carried out using the Ijarah contract, namely one party (owner or tenant) grants the right to use goods or services to another party for a certain period of time in return for the agreed payment. The Ijarah contract carried out between the owner and tenant of the plantation land uses a rental system based on the planting period in one year which has a planting period twice a year with the condition that there is clarity of Ijab and Qabul, there is an agreement, justice without Ghrarar and ethics and Sharia principles.